Emotionalization in Science Communication: The Impact of Narratives and Visual Representations on Knowledge Gain and Risk Perception - Flemming, Danny; Cress, Ulrike; Kimmig, Sophia; Brandt, Miriam; Kimmerle, Joachim (Frontiers in Communication, 2018)
The communication of scientific information plays an increasingly important role for scientists and scientific institutions. This is especially true of institutions in the field of biodiversity and conservation research, since the transfer of research results to the public is a prerequisite for decision-making, and the success of conservation measures often depends on public acceptance or active contribution. To have the desired impact, science communication in the context of human-wildlife interactions must enable recipients to (1) gain valid knowledge, (2) form an attitude toward the subject matter, and (3) develop an adequate understanding of the risks and dangers associated with human-wildlife interactions, which are usually overestimated by the general public. Using the topic of foxes in urban habitats, we investigated the role of emotionalization in science communication. In a laboratory experiment with 127 university students (91 females), we manipulated textual and visual features in an information brochure about foxes and examined their impact on people’s knowledge gain, attitude development, and modified risk perception. In particular, we compared a narrative presentation to a non-narrative list of facts and examined the use of photographs of young foxes. We found a positive development in all of the outcome variables from the pre- to the posttest (more knowledge, more positive attitude, lower risk perception). We also found an interaction effect of text type and visualization on knowledge gain that highlighted the importance of the fit between text type and visualization. In contrast to our expectations, we did not find any differential effects of specific treatments on attitude development. Finally, we found a main effect of text type on modified risk perception, indicating less reduction of risk perception with a narrative article than with a fact list. We discuss our findings with respect to the role of emotionalization in science communication, stressing that it is particularly important to achieve a suitable fit between textual and visual forms of emotionalization, depending on the goal of communication. We also discuss possible explanations as to why some hypotheses were not supported by the data. In our concluding statements we refer to limitations of the present study and address implications